Algorithms and data structures : 16th International Symposium, WADS 2019, Edmonton, AB, Canada, August 5-7, 2019, Proceedings /: 16th International Symposium, WADS 2019, Edmonton, AB, Canada, August 5-7, 2019, Proceedings. ([2019]) - Unknown
No abstract available